Pengaruh Adaptasi CEO Terhadap Keberlangsungan Bisnis yang Dimoderasi Oleh Usia CEO dan Tingkat Pendidikan CEO Startup Business Mahasiswa Universitas Ciputra Surabaya - Krisnata, Andreas (PERFORMA, 2023)
The quite significant change occurs in the industrial world in globalization era. The industry has undergone a lot of change starting from industry 1.0, 2.0, 3.0, until now has entered industry 4.0. Each change of revolutionary era has its own characteristic. Of course this industry change cannot be separated from the role of Chief Executive Officer (CEO) to adapt because the CEO is the most important figure in determining the strategy to which direction of the business that is run will develop. In addition, the CEO plays the role as determinant of realizing the vision and mission of the business. Therefore, the purpose of this research is to analyze the factor of age and level of education to be the factors that can strengthen or weaken the relation between CEO adaptation towards the strategy that is taken, so can affect the sustainability towards the business. As many as 98 CEO from various business types at Universitas Ciputra Surabaya successfully are obtained through purposive sampling technique. The method that is used to process data by using Partial Least Square-SEM (PLS-SEM). The result that is obtained in this research indicates that CEO adaptation has significant result towards the sustainability of the business. In addition, it is found that the role of CEO age and CEO education level as moderator variables do not have significant effect. Keyword: CEO adaptation, CEO age, CEO education, business continuity